Reform of Quota and Voice in the International Monetary Fund-Draft Report of the Executive Board to the Board of Governors. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This report sets out a proposal for a second-round package of reforms consistent with the framework agreed in the Singapore Resolution and, to that end, recommends that the Board of Governors approve the resolution that is appended to this Report (the "Resolution").
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund; PP; Quota Share; Share; Vote; Singapore